Directions of zero thermal expansion and the peritectic transformation in HfTiO4. (November 2020) - McCormack, Scott J.; Wheeler, William A.; Hulbert, Benjamin S.; Kriven, Waltraud M.
Abstract: The anisotropic infinitesimal coefficients of thermal expansion (CTE) and the peritectic transformation of orthorhombic-HfTiO4 (space group: pbcn, #60) to tetragonal-HfO2 (space group: P42 /nmc, #137) plus liquid at 1980 °C (O-HfTiO4 ⇄ T -HfO2 +L(Hf, Ti, O) ) have been studied by in-situ X-ray powder diffraction from room temperature to complete melting ( 2300 °C) in air, using a Quadrupole Lamp Furnace (QLF) and a Conical Nozzle Levitator (CNL) equipped with a 400 W CO2 laser. Directions of zero thermal expansion were identified in the temperature range 25 – 580 ˚C and visualized in 3D using distorted cones and 2D stereographic projections. The directions of zero thermal expansion change as a function of temperature. The (021) pole of orthorhombic HfTiO4 was identified as having the lowest root mean squared (rms) thermal expansion, 12 times lower than the highest rms thermal expansion direction [100] over the temperature range: 25 – 580 ˚C. The topotactic, peritectic transformation has been fully described by extracting the lattice correspondence, lattice variant deformation and a structural motif (grouping of cations) that relates the two structures at the transformation temperature. Symmetry decomposition was performed to show that the orthorhombic-HfTiO4 and tetragonal-HfO2 structures are simply related by polyhedral rotations and cation oxygen coordination changes, in addition to a slight adjustment in cation positions. Graphical abstract: Image, graphical abstract